Simulasi Penerapan Mikrokontroller At89c51 Dalam Proses Penyortiran Balok Kayu Berdasarkan Kriteria Panjang Dan Ketebalan - Arief Hendra Saptadi; Vita Nurdinawati (Jenderal Soedirman University, 2008)
The main problem on sorting out the wood logs in traditional wood industry was that the process should be done manually. Hence, it required an automated system to perform sorting process with a higher precision level. The purpose of this research was to create a simulation of automated wood log sorting process based on specified length and thickness. The sorting system consisted of AT89C51 microcontroller system, keypad (in order to enter the required value of length and thickness), LCD (in order to display the result of sorting process), conveyor belt, two pairs of light sensor (consisting of photodiode and LED, each), and three DC motors which were driven by five relay circuits. At the beginning of sorting process, an operator was to type the selection range (i.e. the minimum and maximum value of required length and thickness) via the keypad provided. The wood log mounted on conveyor belt would be measured by light sensors to determine the value of length and thickness. Based on the values, AT89C51 microcontroller system would then compare them to the selection range. If the log being sorted out fulfilled the requirements, it would be directed to